Tracking the role of subducted magnesite in serpentinite to transport incompatible elements into the deep mantle - Yuan-Ru Qu; Hamed Gamaleldien; Tim E. Johnson; Jianfeng Ma; Tamer Abu-Alam; Denis Fougerouse; Steven M. Reddy; Noreen.J. Evans (Lithos, 2026)

Immune system evaluation of Echinacea Purpurea root extract in female Harlan Sprague Dawley (Hsd:Sprague Dawley SD) rats - Victor J. Johnson; Suramya Waidyanatha; Dori R. Germolec; Michelle C. Cora; Mark F. Cesta; Keith R. Shockley; Angela Jeffers; Karen Cimon; Esra Mutlu; Tim Cristy; Jessica Pierfellice; Michael I. Luster; et al. (Food and Chemical Toxicology, 2026)

Site Index Trends in Pine Plantations of the Southeastern United States: Interactions with Soil and Ownership - Valentina R. Vaney; Daniel J. Johnson; Tim Martin; Geraldine Klarenberg; Jason Vogel (Journal of Forestry, 2026)

Camera traps and acoustic approaches are needed to monitor Malagasy seed dispersers - Niaina Nirina Mahefa Andriamavosoloarisoa; Joris P. G. M. Cromsigt; Tim R. Hofmeester; Steig E. Johnson; Patrik Lauha; Nicole Scholte Lubberink; Pamela R. Narváez-Torres; Dimby Raharinjanahary; Eric Tsiriniaina Rajoelison; Linah Randrianaina; Famenontsoa Rojomalala Fiononana Ratsimba; Onja H. Razafindratsima; et al. (Biodiversity and Conservation, 2026)
Despite extensive conservation efforts worldwide, biodiversity loss continues, particularly in tropical regions. It is, therefore, essential to develop biodiversity monitoring methods that can be effectively scaled up in both time and space, enabling wildlife managers to quickly assess and respond to changes in populations or communities. We explored the effectiveness of combining camera traps with acoustic methods to survey seed dispersing birds and mammals. We deployed arboreal and terrestrial camera traps alongside AudioMoth sound recorders with varying recording schedules to survey 220 sampling locations across five distinct sites in Madagascar’s eastern humid forests, though acoustic analyses were limited to one site. Based on all three methods (arboreal, terrestrial camera trap and AudioMoths), we successfully identified 78 % of the seed disperser species assumed to be present at our sites. The species accumulation curves estimated higher species richness for arboreal cameras than for terrestrial cameras, and for mature protected forests compared to other habitats. Species composition differed between the two types of cameras, while bird species composition in Ranomafana differed between camera traps and AudioMoths. Arboreal camera traps detected more frugivorous primate, bird, and bat species while terrestrial camera traps detected more ground-dwelling vertebrate species. Where both cameras and AudioMoths were deployed species composition differed significantly, with AudioMoths detecting more vocal bird species. These results highlight the need for a combined approach to fully survey the seed-dispersal community, along with further development of acoustic analysis techniques for future studies.

Iron and zinc isotopic insights into the formation of Archean continental crust - Jianfeng Ma; Hamed Gamaleldien; Robert H. Smithies; Tim Johnson; Yuan-Ru Qu; Sheng-Ao Liu; Christopher L. Kirkland (Earth and Planetary Science Letters, 2026)

Neoarchean ultrahigh-temperature metamorphism in the Saglek–Hebron Complex, northern Labrador - Meiyun Huang; Shujuan Jiao; Tim E. Johnson; Jonathan O’Neil; Hanika Rizo; Chris Clark; Zhongwu Lan; Qiuli Li; Jinghui Guo (Precambrian Research, 2026)

Geographic Variation in the Diet of Red Knot ( Calidris canutus ) Chicks Reflects Local Prey Communities - Reinier Blok; Mikhail K. Zhemchuzhnikov; Tim Oortwijn; Jannik Hansen; James A. Johnson; Niels Martin Schmidt; Judith D. L. van Bleijswijk; Elena Zhemchuzhnikova; Thomas K. Lameris; Jeroen Reneerkens; Tom Versluijs; Zachary M. Pohlen; et al. (Journal of Biogeography, 2026)
Aim To describe and compare the diets of an Arctic‐breeding shorebird, the Red Knot ( Calidris canutus ), across three geographically distinct breeding sites. We aimed to document the dietary patterns and identify key prey groups that characterise each population's foraging ecology. Location Northwest Alaska (Nome), Northeast Greenland (Zackenberg) and North‐Central Russia (Taimyr Peninsula). Taxon Red Knot (Aves: Calidris canutus ). Methods We characterised chick diet by applying COI DNA metabarcoding to faecal samples and quantified local prey availability using standardised arthropod pitfall trap sampling at the three Arctic breeding sites. We described and compared the dietary composition, diversity, and relative abundance of major prey taxa among locations. Results We found substantial geographical variation in the chick diet. Diptera was a major food source across all locations, but its constituent families and importance varied. In Taimyr, the diet was dominated by Tipulidae (crane flies), comprising nearly 50% of the relative read abundance (RRA). In contrast, chicks in Greenland consumed a diet dominated by Diptera (87.8%) that almost entirely lacked Tipulidae. The diet in Alaska was the most diverse, with balanced contributions from Diptera (28.5%), Coleoptera (22.3%), and Lepidoptera (23.2%), along with other invertebrate groups, including Agriolimacidae. Main Conclusions The diet of Red Knot chicks differed among the study sites and appeared to be shaped primarily by the local availability of arthropod prey. This foraging plasticity allows the species to breed successfully across a wide circumpolar range with a heterogeneous prey landscape. However, this distinct specialisation on local prey, particularly Tipulidae in Taimyr, may create a critical phenological vulnerability.

Globalism, localism and blue food systems – How can cross-scale tensions be reduced? A production perspective from UK seafood stakeholders - Alex J. Caveen; Bryce D. Stewart; Cameron Moffat; Daniel Skerritt; Estelle Jones; Huw Thomas; Lara Funk; Magnus Johnson; Mike Cohen; Michael Roach; Neil A. Auchterlonie; Samuel Peacock; et al. (Marine Policy, 2025)

Unique thermal mixing patterns in Lake Ontario revealed by novel year‐round observations of thermal stratification - Mathew Wells; Tim Johnson; Rylie Robinson; Jon Midwood; Yulu Shi; Sarah Larocque; Adam Eddie; Brian O'Malley; Kyle Morton; Dimitry Gorsky; Bruce Tufts (Limnology and Oceanography, 2025)
Year‐round records of thermal stratification in the Great Lakes are rare, and there are few observations of thermal stratification during winter. In this paper, we analyze temperature data from 13 temperature logger chains and from over 130 benthic acoustic receivers that were deployed across Lake Ontario for 2 yr. The timing and duration of the fall overturn correlate with the local average water depth, and shallow sites ( 100 m depths). Likewise, in spring, the shallow sites warm faster. Lake Ontario has partial ice cover, so wind‐driven mixing stirs the water column throughout winter, and inverse thermal stratification is largely absent. The depth‐averaged winter water temperatures vary between 0°C and 4°C, with the coldest temperatures (near 0.1°C) found in the shallow Kingston basin and warmest temperatures (near 4°C) at sites near the 244 m deep Rochester Basin. Lake Ontario appears to be a warm monomictic lake, rather than having a dimictic mixing pattern as previously described—there is no sustained ice cover or inverse stratification that inhibits vertical mixing in winter. Winter is a poorly understood season for many aquatic processes, including fish bioenergetics, fish distribution, biochemical processes, invertebrate distribution, and production. Moreover, the lack of knowledge of winter has hampered the use of correct initial conditions for running large lake hydrodynamic models.

Not all Neoproterozoic continental crust exposed in the Sulu belt was deeply subducted - Zhuocheng Wang; Lu Wang; Michael Brown; Tim E. Johnson; Christopher L. Kirkland; Chris Clark; Eleanore Blereau (Lithos, 2025)

Garnet as a reliable timekeeper in Archean polymetamorphic terranes - Jonas Kaempf; Chris Clark; Tim E. Johnson; Mudlappa Jayananda; Martin Hand; Krishnan Sajeev (Earth and Planetary Science Letters, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Design and implementation of resistive grout for cross-borehole electrical imaging - Jonathan Thomle; Kelsey Peta; Lirong Zhong; Judy Robinson; Tim Johnson (Journal of Applied Geophysics, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Understanding the implications of climate change for Australia’s surface water resources: Challenges and future directions - Conrad Wasko; Clare Stephens; Tim J. Peterson; Rory Nathan; Acacia Pepler; Suresh Hettiarachchi; Elisabeth Vogel; Fiona Johnson; Seth Westra (Journal of Hydrology, 2024)

Trends and Variability in Earth’s Energy Imbalance and Ocean Heat Uptake Since 2005 - Maria Z. Hakuba; Sébastien Fourest; Tim Boyer; Benoit Meyssignac; James A. Carton; Gaël Forget; Lijing Cheng; Donata Giglio; Gregory C. Johnson; Seiji Kato; Rachel E. Killick; Nicolas Kolodziejczyk; et al. (Surveys in Geophysics, 2024)
Earth’s energy imbalance (EEI) is a fundamental metric of global Earth system change, quantifying the cumulative impact of natural and anthropogenic radiative forcings and feedback. To date, the most precise measurements of EEI change are obtained through radiometric observations at the top of the atmosphere (TOA), while the quantification of EEI absolute magnitude is facilitated through heat inventory analysis, where ~ 90% of heat uptake manifests as an increase in ocean heat content (OHC). Various international groups provide OHC datasets derived from in situ and satellite observations, as well as from reanalyses ingesting many available observations. The WCRP formed the GEWEX-EEI Assessment Working Group to better understand discrepancies, uncertainties and reconcile current knowledge of EEI magnitude, variability and trends. Here, 21 OHC datasets and ocean heat uptake (OHU) rates are intercompared, providing OHU estimates ranging between 0.40 ± 0.12 and 0.96 ± 0.08 W m −2 (2005–2019), a spread that is slightly reduced when unequal ocean sampling is accounted for, and that is largely attributable to differing source data, mapping methods and quality control procedures. The rate of increase in OHU varies substantially between − 0.03 ± 0.13 (reanalysis product) and 1.1 ± 0.6 W m −2 dec −1 (satellite product). Products that either more regularly observe (satellites) or fill in situ data-sparse regions based on additional physical knowledge (some reanalysis and hybrid products) tend to track radiometric EEI variability better than purely in situ-based OHC products. This paper also examines zonal trends in TOA radiative fluxes and the impact of data gaps on trend estimates. The GEWEX-EEI community aims to refine their assessment studies, to forge a path toward best practices, e.g., in uncertainty quantification, and to formulate recommendations for future activities.

Eoarchean granulite-facies metamorphism in the Itsaq Gneiss Complex, southwest Greenland - Julian Alfing; Tim E. Johnson; Jonas Kaempf; Michael Brown; Kristoffer Szilas; Kai Rankenburg; Chris Clark (Earth and Planetary Science Letters, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Archean UHT metamorphism with counterclockwise P–T path: Insights from pelitic granulites from East Hebei, North China Craton - Ting Liu; Chunjing Wei; Tim E. Johnson (Gondwana Research, 2024)

Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.

Advancing botanical safety: A strategy for selecting, sourcing, and characterizing botanicals for developing toxicological tools - Suramya Waidyanatha; Bradley J. Collins; Tim Cristy; Michelle Embry; Stefan Gafner; Holly Johnson; Josh Kellogg; Julie Krzykwa; Siheng Li; Constance A. Mitchell; Esra Mutlu; Sarah Pickett; et al. (Food and Chemical Toxicology, 2024)

Population parameters and conservation implications for one of the world's rarest marine fishes, the red handfish ( Thymichthys politus ) - Tyson J. Bessell; Rick D. Stuart‐Smith; Olivia J. Johnson; Neville S. Barrett; Tim P. Lynch; Andrew J. Trotter; Jemina Stuart‐Smith (Journal of Fish Biology, 2024)
Population estimates are required for effective conservation of many rare marine species, but can be difficult to obtain. The critically endangered red handfish ( Thymichthys politus ) is a coastal anglerfish known only from two fragmented populations in southeast Tasmania, Australia. It is at a high risk of extinction due to low numbers, loss of habitat, and the impacts of climate change. To aid conservation efforts, we provide the first empirical population size estimates of red handfish and investigate other important aspects of the species' life history, such as growth, habitat association, and movement. We surveyed both red handfish local populations via underwater visual census on scuba over 3 years and used photographic mark‐recapture techniques to estimate biological parameters. In 2020, the local adult population size was estimated to be 94 (95% confidence interval [CI] 40–231) adults at one site, and 7 (95% CI 5–10) at the other site, suggesting an estimated global population of 101 adults. Movement of individuals was extremely limited at 48.5 m (± 77.7 S.D. ) per year. We also found evidence of declining fish density, a declining proportion of juveniles, and increasing average fish size during the study. These results provide a serious warning that red handfish are likely sliding toward extinction, and highlight the urgent need to expand efforts for ex situ captive breeding to bolster numbers in the wild and maintain captive insurance populations, and to protect vital habitat to safeguard the species' ongoing survival in the wild.

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Effects of glacier retreat upon glacier-groundwater coupling and biogeochemistry in Central Svalbard - Andrew Hodson; Gabrielle Kleber; Jack Johnson; Michael Lonardi; Chiara Petroselli; Tim Dixon; Simon Bottrell (Journal of Hydrology, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Middle Palaeolithic occupation of the southern North Sea Basin: evidence from the Sandscaping sediments emplaced on the beach between Bacton and Walcott, Norfolk, UK - Rob Davis; Nick Ashton; Rachel Bynoe; John Craven; Rob Ferguson; Ian Gardner; Tim Grimmer; Claire Harris; Marcus Hatch; Colin Johnson; Joanne Leonard; Simon Lewis; et al. (Journal of Quaternary Science, 2023)
During the summer of 2019, the Bacton to Walcott Coastal Management Scheme involved the emplacement on to the foreshore of 1.8 million cubic metres of sand and gravel dredged from the submerged sediments of the Palaeo‐Yare in the southern North Sea 11 km off Great Yarmouth. During the following 2‐year period, an active group of collectors identified Palaeolithic artefacts eroding from these sediments, including Levallois cores and flakes, and cordiform handaxes. In this paper, we present an analysis of the lithic artefacts, and consider the relationships between the different elements of the assemblage. We discuss its significance in the context of the Middle Palaeolithic record of northwest Europe and the light it shines on the human occupation of the submerged landscape of the southern North Sea during the later Middle Pleistocene. Interrogation of beach survey data shows the reworking of these sediments to the southeast towards Happisburgh where archaeologically significant exposures of the Cromer Forest‐bed Formation are located. The implications of the introduction of a Middle Palaeolithic assemblage to this stretch of the North Norfolk Coast are considered, highlighting the importance of continuing dialogue between researchers, local authorities and local communities for capturing information and monitoring this critical Palaeolithic resource.

Evaluation of biopesticides for the control of Erwinia amylovora in apple and pear - S. Tianna DuPont; Kerik Cox; Ken Johnson; Kari Peter; Tim Smith; Misbakhul Munir; Aina Baro (Journal of Plant Pathology, 2023)
With increasing organic acreage and scrutiny of antibiotics use, alternatives to antibiotics for the control of Erwinia amylovora are of interest to stakeholders. At the same time failures of minimally tested, newly marketed products have resulted in severe infections leading to costly tree and orchard removal. We evaluated antibiotic alternatives in 8 Washington, 3 Oregon, 3 New York and 2 Pennsylvania field experiments conducted 2013 to 2022. Antibiotic alternatives included essential oils (thyme and cinnamon extracts), mineral compounds (potassium aluminum sulfate), oxidizers (peracetic acid-peroxide), soluble coppers (copper octanoate, copper hydroxide, copper sulfate pentahydrate), and biological controls ( Aureobasidium pullulans , Bacillus subtilis , bacteriophage). Studies were conducted in ‘Bartlett’ and ‘dAnjou’ pear, ‘Gala’, ‘Cameo,‘ and ‘Red Delicious’ apple with 4 to 6 single-tree replicates arranged in a randomized complete block inoculated with E. amylovora at 80–100% bloom. In summary analysis of 8 Washington trials Alum (potassium aluminum sulfate), Blossom Protect ( A. pullulans ) and several copper products (Previsto, Mastercop, Instill) provided good disease suppression of 70–73% similar to antibiotic checks. Several essential oil, copper, and peracetic acid-peroxide and biological products (Serenade Opti, Cueva, Oxidate 5.0, Jet Ag, Thyme Guard and Thymox) provided intermediate disease suppression between 45 and 62% significantly better than the water-treated control. In multistate trials Alum with 2–3 applications provided good control in most experiments (means 2019: WA 79%, NY 77%, PA 57%; 2020: OR 86%, NY 65%, WA 28%; 2021: NY 87%, WA 50%). Essential oils with 3–4 applications provided intermediate control NY 2021 81% control 23% thyme oil, 70–85% control NY 2020, 2021 60% cinnamon oil.

3D Time-Lapse Electrical Resistivity Imaging of Rock Damage Patterns and Gas Flow Paths Resulting from Two Underground Chemical Explosions - Tim C. Johnson; H. A. Knox; C. Strickland; C. Johnson; J. Lowrey; D.P. Sprinkle; D. Linneman; V. Vermeul; E. Robey; K. Chojnicki; M. Ingraham; J. Feldman; et al. (Pure and Applied Geophysics, 2023)
Rock damage from underground nuclear explosions (UNEs) has a strong influence on sub-surface gas movement and on seismic waveform characteristics, both of which are used to detect UNEs. Although advanced numerical simulation capabilities exist to predict rock damage patterns and corresponding detection signals, those predictions are dependent on (generally) unknown properties of the host rock. For example, the effects of in-situ mechanical heterogeneities on the explosively generated damage/fractures that provide gas flow pathways to the surface are not well understood, due largely to the difficulty in accessing and characterizing the near-source region. In this paper we demonstrate the emerging use of electrical resistivity tomography (ERT) for imaging rock damage and gas flow patterns resulting from two relatively small-scale underground chemical explosions. Pre-explosion ERT and crosshole seismic imaging revealed a natural fracture zone within the test bed. Post-explosion imaging revealed that the damage zone was non-symmetric and was focused primarily within the pre-existing fracture zone, located 10 m above the first explosion and 5 m above the second explosion. Time-lapse ERT imaging of heated air injected into the detonation borehole revealed the primary gas flow paths to be within the upper margin of the same primary damage zone. These results point to the utility of ERT imaging for understanding rock damage and gas flow patterns under experimental conditions, and to the importance of understanding the effects of geologic heterogeneity on UNE detection signals, particularly gas surface breakthrough times.

The tempo of back-arc basin evolution: Insights from the early Paleozoic Proto-Tethyan North Qilian orogenic belt, northeastern Tibet - Dong Fu; Bo Huang; Simon A. Wilde; Tim E. Johnson; Ali Polat; Brian F. Windley; Zhaochu Hu; Zhipeng Zhou; Timothy M. Kusky (Earth and Planetary Science Letters, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Predators, Disease, and Environmental Change in the Nearshore Ecosystem: Mortality in Southern Sea Otters (Enhydra lutris nereis) From 1998–2012 - Melissa A. Miller; Megan E. Moriarty; Laird Henkel; Martin Tim Tinker; Tristan L. Burgess; Francesca I. Batac; Erin Dodd; Colleen Young; Michael D. Harris; David A. Jessup; Jack Ames; Patricia A. Conrad; et al. (Frontiers in Marine Science, 2020)
We compiled findings from 15 years (1998–2012) of southern sea otter ( Enhydra lutris nereis ) necropsies, incorporating data from 560 animals. Sensitive diagnostic tests were used to detect biotoxins, bacteria, parasites and fungi. Methods to classify primary and contributing causes of death (COD) and sequelae utilized an updated understanding of health risks affecting this population. Several interesting patterns emerged, including identification of coastal regions of high mortality risk for sea otter mortality due to shark bite, cardiomyopathy, toxoplasmosis, sarcocystosis, acanthocephalan peritonitis and coccidioidomycosis. We identified demographic attributes that enhanced the risk of disease in relation to age, sex, and reproductive stage. Death due to white shark ( Carcharodon carcharias ) bite increased dramatically during the study period and was the most common primary COD. However, when primary and contributing COD were combined, the most prevalent COD was infectious disease (affecting 63% of otters), especially fatal infections by acanthocephalans ( Profilicollis spp.) and protozoa (e.g., Sarcocystis neurona and Toxoplasma gondii ). Fatal bacterial infections were also extremely common as a primary process or a sequela, affecting 68% of examined otters. Substantial advances were made in identifying sea otters that died following exposure to the pervasive marine neurotoxin domoic acid (DA), and DA intoxication was conservatively estimated as a primary or contributing COD for 20% of otters. Cardiomyopathy was also highly prevalent as a primary or contributing COD (41%) and exhibited significant associations with DA intoxication and protozoal infection. For adult and aged adult females in late pup care through post-weaning at the time of death, 83% had end lactation syndrome (ELS) as a primary or contributing COD. This comprehensive longitudinal dataset is unique in its depth and scope. The large sample size and extensive time period provided an opportunity to investigate mortality patterns in a changing environment and identify spatial and temporal disease “hot spots” and emerging threats. Our findings will help improve estimates of population-level impacts of specific threats and optimize conservation and environmental mitigation efforts for this threatened species.

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Unnatural selection of salmon life histories in a modified riverscape - Anna M. Sturrock; Stephanie M. Carlson; John D. Wikert; Tim Heyne; Sébastien Nusslé; Joseph E. Merz; Hugh J. W. Sturrock; Rachel C. Johnson (Global Change Biology, 2020)
Altered river flows and fragmented habitats often simplify riverine communities and favor non‐native fishes, but their influence on life‐history expression and survival is less clear. Here, we quantified the expression and ultimate success of diverse salmon emigration behaviors in an anthropogenically altered California river system. We analyzed two decades of Chinook salmon monitoring data to explore the influence of regulated flows on juvenile emigration phenology, abundance, and recruitment. We then followed seven cohorts into adulthood using otolith (ear stone) chemical archives to identify patterns in time‐ and size‐selective mortality along the migratory corridor. Suppressed winter flow cues were associated with delayed emigration timing, particularly in warm, dry years, which was also when selection against late migrants was the most extreme. Lower, less variable flows were also associated with reduced juvenile and adult production, highlighting the importance of streamflow for cohort success in these southernmost populations. While most juveniles emigrated from the natal stream as fry or smolts, the survivors were dominated by the rare few that left at intermediate sizes and times, coinciding with managed flows released before extreme summer temperatures. The consistent selection against early (small) and late (large) migrants counters prevailing ecological theory that predicts different traits to be favored under varying environmental conditions. Yet, even with this weakened portfolio, maintaining a broad distribution in migration traits still increased adult production and reduced variance. In years exhibiting large fry pulses, even marginal increases in their survival would have significantly boosted recruitment. However, management actions favoring any single phenotype could have negative evolutionary and demographic consequences, potentially reducing adaptability and population stability. To recover fish populations and support viable fisheries in a warming and increasingly unpredictable climate, coordinating flow and habitat management within and among watersheds will be critical to balance trait optimization versus diversification.

Review of infectious agent occurrence in wild salmonids in British Columbia, Canada - Beibei Jia; Marina K. V. C. Delphino; Babafela Awosile; Tim Hewison; Patrick Whittaker; Diane Morrison; Mykolas Kamaitis; Ahmed Siah; Barry Milligan; Stewart C. Johnson; Ian A. Gardner (Journal of Fish Diseases, 2020)
Wild Pacific salmonids (WPS) are economically and culturally important to the Pacific North region. Most recently, some populations of WPS have been in decline. Of hypothesized factors contributing to the decline, infectious agents have been postulated to increase the risk of mortality in Pacific salmon. We present a literature review of both published journal and unpublished data to describe the distribution of infectious agents reported in wild Pacific salmonid populations in British Columbia (BC), Canada. We targeted 10 infectious agents, considered to potentially cause severe economic losses in Atlantic salmon or be of conservation concern for wild salmon in BC. The findings indicated a low frequency of infectious hematopoietic necrosis virus, piscine orthoreovirus, viral haemorrhagic septicaemia virus, Aeromonas salmonicida , Renibacterium salmoninarum , Piscirickettsia salmonis and other Rickettsia‐like organisms, Yersinia ruckeri , Tenacibaculum maritimum and Moritella viscosa . No positive results were reported for infestations with Paramoeba perurans in peer‐reviewed papers and the DFO Fish Pathology Program database. This review synthesizes existing information, as well as gaps therein, that can support the design and implementation of a long‐term surveillance programme of infectious agents in wild salmonids in BC.

Navigating Complexities: Agent-Based Modeling to Support Research, Governance, and Management in Small-Scale Fisheries - Emilie Lindkvist; Nanda Wijermans; Tim M. Daw; Blanca Gonzalez-Mon; Alfredo Giron-Nava; Andrew F. Johnson; Ingrid van Putten; Xavier Basurto; Maja Schlüter (Frontiers in Marine Science, 2020)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Ocean Warming: From the Surface to the Deep in Observations and Models - Paul Durack; Peter Gleckler; Sarah Purkey; Gregory Johnson; John Lyman; Tim Boywe (Oceanography, 2018)

Rare Earth Element Distribution in the NE Atlantic: Evidence for Benthic Sources, Longevity of the Seawater Signal, and Biogeochemical Cycling - Kirsty C. Crocket; Emily Hill; Richard E. Abell; Clare Johnson; Stefan F. Gary; Tim Brand; Ed C. Hathorne (Frontiers in Marine Science, 2018)

The stresses and dynamics of smallholder coffee systems in Jamaica’s Blue Mountains: a case for the potential role of climate services - Zack Guido; Tim Finan; Kevon Rhiney; Malgosia Madajewicz; Valerie Rountree; Elizabeth Johnson; Gusland McCook (Climatic Change, 2018)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

Determination of PCB Elimination Coefficients in Round Goby and Tubenose Goby - Xin Sun; Tim B. Johnson; Ken G. Drouillard (Bulletin of Environmental Contamination and Toxicology, 2016)

Partitioning the effects of habitat fragmentation on rodent species richness in an urban landscape - Alex M. Johnson; Tim J. Karels (Urban Ecosystems, 2016)

Impacts of eucalypt plantation management on soil faunal communities and nutrient bioavailability: trading function for dependence? - Tiffany J. Aslam; Tim G. Benton; Uffe N. Nielsen; Scott N. Johnson (Biology and Fertility of Soils, 2015)

Unravelling the complexities in high-grade rocks using multiple techniques: the Achankovil Zone of southern India - Richard J. M. Taylor; Chris Clark; Tim E. Johnson; M. Santosh; Alan S. Collins (Contributions to Mineralogy and Petrology, 2015)

Land management between crops affects soil inorganic nitrogen balance in a tropical rice system - Naomi S. Wells; Tim J. Clough; Sarah E. Johnson-Beebout; Roland J. Buresh (Nutrient Cycling in Agroecosystems, 2014)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Trends, current understanding and future research priorities for artisanal coral reef fisheries research - Ayana E Johnson; Joshua E Cinner; Marah J Hardt; Jennifer Jacquet; Tim R McClanahan; James N Sanchirico (Fish and Fisheries, 2013)
Artisanal coral reef fisheries provide food and employment to hundreds of millions of people in developing countries, making their sustainability a high priority. However, many of these fisheries are degraded and not yielding their maximum socioeconomic returns. We present a literature review that evaluates foci and trends in research effort on coral reef fisheries. We describe the types of data and categories of management recommendations presented in the 464 peer‐reviewed articles returned. Identified trends include a decline in articles reporting time‐series data, fish catch biomass and catch‐per‐unit effort, and an increase in articles containing bycatch and stakeholder interview data. Management implications were discussed in 80% of articles, with increasing frequency over time, but only 22% of articles made management recommendations based on the research presented in the article, as opposed to more general recommendations. Key future research priorities, which we deem underrepresented in the literature at present, are: (i) effectiveness of management approaches, (ii) ecological thresholds, trade‐offs and sustainable levels of extraction, (iii) effects of climate change, (iv) food security, (v) the role of aquaculture, (vi) access to and control of fishery resources, (vii) relationships between economic development and fishery exploitation, (viii) alternative livelihoods and (ix) integration of ecological and socioeconomic research.

A Statistically Based Acute Ischemia Detection Algorithm Suitable for an Implantable Device - Bruce Hopenfeld; M. Sasha John; Tim A. Fischell; Steven R. Johnson (Annals of Biomedical Engineering, 2012)

Genetic discontinuity among regional populations of Lophelia pertusa in the North Atlantic Ocean - Cheryl L. Morrison; Steve W. Ross; Martha S. Nizinski; Sandra Brooke; Johanna Järnegren; Rhian G. Waller; Robin L. Johnson; Tim L. King (Conservation Genetics, 2011)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

What's Next for Salinity? - Tim Boyer; Jim Carton; Yi Chao; Arnold Gordon; Greg Johnson; Gary Lagerloef; Bill Large; Steve Riser; Ray Schmitt (Oceanography, 2008)

Small-Scale Chemical Changes Caused by In-stream Limestone Sand Additions to Streams - Jeffrey A. Simmons; Tim Andrew; Andrew Arnold; Neodesha Bee; Joshua Bennett; Miriam Grundman; Kelsy Johnson; Russell Shepherd (Mine Water and the Environment, 2006)

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

New intragenic deletions in the Phex gene clarify X-linked hypophosphatemia-related abnormalities in mice - Leona H. Gagnon; Joiel D. Bauschatz; Muriel T. Davisson; Linda L. Washburn; Leah Rae Donahue; Tim M. Strom; Eva M. Eicher; Kenneth R. Johnson; Victoria E. Guido; Bettina Lorenz-Depiereux; Qing Yin Zheng (Mammalian Genome, 2004)

Investigations in commonness and rarity: a comparative analysis of co‐occurring, congeneric Mexican trees - Colleen K. Kelly; Helena Banyard Smith; Yvonne M. Buckley; Rebecca Carter; Miguel Franco; William Johnson; Tim Jones; Ben May; Rubèn Pèrez Ishiwara; Alfredo Pèrez‐Jimènez; Arturo Solis Magallanes; Helen Steers; et al. (Ecology Letters, 2001)
Population size distributions were examined for 12 species of trees co‐occurring at Chamela Biological Station in Jalisco, Mexico. Species had been selected as congeneric pairs and trios similar in gross morphology and ecology in order better to identify correlates of relative abundance. Rarer species were found unanimously to have more irregular distributions of individuals among size classes than more common species when distributions were compared to a smooth, descending curve constructed from population mean stem diameters (an exponential distribution). Examination among species of patterns of deviation from these corresponding smooth distributions indicates that the most reasonably inferred cause for the observed pattern is consistent differences in degree of fluctuation in recruitment into adult size classes. These results thereby suggest a demographic difference between locally rarer and more common species that may be generally associated with observed differences in relative abundance and indicate a focus for management of rarity in forest trees.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)